2016
DOI: 10.1016/j.chroma.2016.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cellular glutathione:glutathione disulfide ratio in prostate cancer cells by high performance liquid chromatography with electrochemical detection

Abstract: A validated method has been developed for the simultaneous measurement of reduced and oxidized glutathione in de-proteinised cellular extracts. This has been used to compare models of malignant and non-malignant human prostate cell lines. Analysis of LNCaP and DU145 cells showed a glutathione to glutathione disulfide ratio of 8:1 and 32:1 respectively, whilst the control cell line, PZ-HPV7 displayed a ratio of 93:1. Results indicate that the more aggressive phenotype displays adaptation to increased oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 38 publications
1
16
0
1
Order By: Relevance
“…The results demonstrated that the more aggressive phenotype of prostate cancer cells shows adaptation to increased oxidative stress via up-regulation of glutathione turnover [32]. To the extent of our knowledge, there is no literature evaluating the relationship between thiol and PSA levels.…”
Section: Discussionmentioning
confidence: 94%
“…The results demonstrated that the more aggressive phenotype of prostate cancer cells shows adaptation to increased oxidative stress via up-regulation of glutathione turnover [32]. To the extent of our knowledge, there is no literature evaluating the relationship between thiol and PSA levels.…”
Section: Discussionmentioning
confidence: 94%
“…The amount of GSH present in the ASF was higher than previously found; possibly due to 2 hours re-incubation of confluent cells in fresh medium employed before harvesting. However the presence of significant quantities of cysteine (which usually quickly incorporated into GSH) and cysteinylglycine indicates that abnormal/aberrant GSH metabolic pathways exist in this tumor cell line [19]. In the normal cellular synthesis of GSH the only cysteinyl dipeptide involved is γ-glutamylcysteine; GSH synthetase adds glycine to this to give the tripeptide.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of analytical methods have been established for GSH measurement, including high-performance liquid chromatography [5], mass spectrometry [6], surface enhanced Raman scattering [7], enzyme-linked immunosorbent assay [8], electrochemical analysis [9], and fluorescence spectroscopy [10]. Fluorescence spectrometry has been found to be a powerful tool for GSH detection because of its simplicity, high sensitivity, good flexibility, and nondestructive readout [11,12].…”
Section: Introductionmentioning
confidence: 99%